A study of disability and socio-economic impact of mental morbidities from the state of Madhya Pradesh, India - Vijender Singh; Roshan F. Sutar; Suruchi Gupta; Abhijit P. Pakhare; Arun M. Kokane; B. A. Aravind; Gopalkrishna Gururaj; Mathew Varghese; Vivek Benegal; Girish N. Rao (Indian Journal of Psychiatry)
Background: Disability associated with mental illness has a disproportionate impact on the work, social, and family responsibilities of an individual toward society. The evidence for disability in mental illnesses would help the clinician, caregivers, policymakers, and various stakeholders to come up with sustainable solutions not only to help fill the existing gaps in care but also to develop new avenues as per the specific needs of the population of Madhya Pradesh (MP). Aim: To estimate the burden of disability related to mental illnesses in the state of MP. Materials and Methods: A multi-site cross-sectional study was conducted in 2015–16 as part of National Mental Health Survey among adults above 18 years of age. Samples were selected using multi-stage, stratified, random cluster sampling based on probability proportionate to size. Six tehsils with one urban metro out of four districts from a total of 50 districts were selected in the state of MP. The Sheehan Disability Scale and socio-economic impact of illness (from selected questions from WHO-Disability Assessment Schedule-2.0) were used to assess mental morbidity and the subjective reporting of disability. Results: The weighted prevalence of disability (n = 1011) was found as 10.2%, 13.1%, and 13.9%, respectively, in work/school, social life, and family/home domains. The weighted prevalence of moderate to extreme disability in the same domains was, respectively, 5.1%, 6.7%, and 7.3%. The presence of common mental disorders (CMDs) increases the odds of self-reported disability in work [odds ratio (OR) 2.48, 95% CI 1.35 to 4.59], social life (OR 2.74, 95% CI 1.50 to 5.07), and family domains (OR 3.03, 95% CI1.62 to 5.74). When combined with common mental disorders, tobacco use disorder further escalates the odds of self-reported disability in all three domains [OR 7.10, confidence interval (CI) 3.15 to 16.37; 4.93, CI 2.19 to 11.28; and 7.10, CI 2.78 to 19.25]. Currently, non-working persons had a higher disability in social life and family life domains (P = 0.003 and P = 0.021), respectively. Conclusion: We report a substantial magnitude of disability in social, work, and family life domains. Participants having CMDs, female gender, and those non-working had more disabilities and would require targeted interventions.